The System of Preparation of Future Teachers for Pedagogical Innovative Activity in General Secondary Schools - Zaripova Matluba Kulfiddinovna (Genius Journals, 2021)
The article focuses on the creation of a favorable innovative environment in the teaching staff, the development of scientific and methodological training of teachers, the orientation of their professional activities to innovative pedagogical processes, their effective involvement in the creation, development, implementation and dissemination of pedagogical innovations.
Keywords: Education; innovation; science; development